Tipificación de las conductas disciplinables más recurrentes en los contadores públicos en Colombia, periodo 2007-2012 (2013)
As regard to ethical behavior in the profession of public accountant it is governed by Acts 43 of 1990 in Chapter IV and the 1314, 2009, and the Code of Ethics of the IFAC in section 150 and some items of National Political Constitution, responsible for ensuring that the accountant's conduct is blameless and upright. The purpose of this paper is to identify what were the disciplinary behaviors in which public accountants incurred in Colombia during the period between 2007 and 2012, by which they have been subject to disciplinary action by the Central Board of Accountants such as disciplinary tribunal of the accounting profession.